REFRACTIVE ERROR AND SQUINT IN PRIMARY SCHOOL CHILDREN - Awan, Abdul Aziz; Aftab, Mohammad; Arif, Salim (Journal of Ayub Medical College Abbottabad, 1995)
1306 school children were screened for refractive errors and squint between September 1991 and September 1994. 2.60% of the children had abnormal cover test. 7.04% of the children were found to have refractive error. Only 36.95% of the children were aware of their refractive error and using glasses. Myopia was the commonest refractive error amounting to 6.127c. Many of the children examined were not aware of their ocular disease.